2014
DOI: 10.1371/journal.pone.0114541
|View full text |Cite
|
Sign up to set email alerts
|

Where Does HIT Fit? An Examination of the Affective Response to High-Intensity Intervals in Comparison to Continuous Moderate- and Continuous Vigorous-Intensity Exercise in the Exercise Intensity-Affect Continuum

Abstract: Affect experienced during an exercise session is purported to predict future exercise behaviour. Compared to continuous moderate-intensity exercise (CMI), the affective response to continuous vigorous-intensity exercise (CVI) has consistently been shown to be more aversive. The affective response, and overall tolerability to high-intensity interval training (HIT), is less studied. To date, there has yet to be a comparison between HIT, CVI, and CMI. The purpose of this study was to compare the tolerability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
291
7
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(331 citation statements)
references
References 36 publications
28
291
7
5
Order By: Relevance
“…Hardcastle et al [16] assert that SIT is too physically demanding for a largely sedentary population, and that low levels of enjoyment and affect elicited by the intense nature of SIT may discourage exercise adherence and motivation. However, the current study and related investigations ( [12][13][14] incorporated HIIT which has a lower metabolic perturbation than SIT. Despite significant physiological differences between these modes of interval training, findings from recent studies showed similar enjoyment between two regimes of HIIT [18] and similar affect between HIIT and SIT [19].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Hardcastle et al [16] assert that SIT is too physically demanding for a largely sedentary population, and that low levels of enjoyment and affect elicited by the intense nature of SIT may discourage exercise adherence and motivation. However, the current study and related investigations ( [12][13][14] incorporated HIIT which has a lower metabolic perturbation than SIT. Despite significant physiological differences between these modes of interval training, findings from recent studies showed similar enjoyment between two regimes of HIIT [18] and similar affect between HIIT and SIT [19].…”
Section: Introductionmentioning
confidence: 79%
“…In a subsequent study in 15 young men (VO 2 max = 47.9 mL/kg/min) [13], repeated 2 min intervals at 100%VO 2 max led to less positive affect and greater fatigue versus MICT consisting of 24 min of cycling at 72%VO 2 max, although enjoyment was similar. In the Jung et al study [14], 44 inactive men and women (VO 2 max = 36 mL/ kg/min) performed in randomized order HIIT consisting of 1 min bouts at 100%Wpeak, and moderate (40 min at 40%Wpeak) and vigorous MICT (20 min at 80%Wpeak). Despite a less positive affect reported in HIIT versus moderate MICT, participants exhibited similar task selfefficacy and greater enjoyment versus vigorous exercise (p = 0.01) and MICT (p = 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…This may (Frazão et al, 2016;Saanijoki et al, 2015), or may not (Freese et al, 2014;Jung et al, 2014) be the case for HIT protocols that rely on many (4-10) longer (30-60 s) sprints, but the ratings of perceived exertion in response to two 20-s sprints as used in the REHIT protocol in the present study appear to be manageable, and the majority of participants (12 out of 16) stated a preference for performing REHIT rather than the walking intervention based on current physical activity recommendations. There is therefore an urgent need to perform further studies examining the efficacy, acceptability, and longer-term adherence to REHIT as a practical 'real-life' intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, direct comparison between SIT (8 × 30 s at 130% maximal work separated by 90 s of recovery, ϳ79% age-predicted maximal heart rate) and HIIT (8 × 60 s at 85% maximal work with 1 min of recovery, ϳ77% age-predicted maximal heart rate) in young active individuals found that the affective responses were similar despite greater blood lactate concentrations and perceived exertion during SIT (Wood et al 2016). Another recent study performed an in-depth exploration of the tolerability and affective responses of HIIT (10 × 1-min bouts at 100% of peak work separated by 1 min of rest, ϳ90% maximal heart rate) compared with MICT (40% peak work, ϳ70% maximal heart rate) and vigorous-intensity continuous exercise (ϳ80% peak work, ϳ90% maximal heart rate) in lean but inactive participants (Jung et al 2014). Affective responses were measured before, during, immediately postexercise, and 20 min postexercise along with task self-efficacy, intentions, enjoyment, and preference (Jung et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study performed an in-depth exploration of the tolerability and affective responses of HIIT (10 × 1-min bouts at 100% of peak work separated by 1 min of rest, ϳ90% maximal heart rate) compared with MICT (40% peak work, ϳ70% maximal heart rate) and vigorous-intensity continuous exercise (ϳ80% peak work, ϳ90% maximal heart rate) in lean but inactive participants (Jung et al 2014). Affective responses were measured before, during, immediately postexercise, and 20 min postexercise along with task self-efficacy, intentions, enjoyment, and preference (Jung et al 2014). Participants reported greater enjoyment of HIIT compared with MICT and vigorous-intensity continuous exercise, with over 50% of participants preferring HIIT.…”
Section: Introductionmentioning
confidence: 99%